Statins for the Treatment of Pulmonary Hypertension in Patients with Chronic Obstructive Pulmonary Disease - Chen, Chung-Yu; Wu, Wen-Ting; Wang, Ya-Ling; Liao, Kuang-Ming (Frontiers in Pharmacology, 2021)
Background: Patients with chronic obstructive pulmonary disease (COPD) are at risk for pulmonary hypertension (PH). The aim of our study was to investigate the benefit of statins for PH in patients with COPD. Methods: The study enrolled 23 million individuals from Taiwan’s population database from January 1, 2002, to December 31, 2017. COPD patients who met the inclusion criteria were enrolled, and patients with lung cancer, less than one year of observation, specific drug therapy for PH and lung transplantation were excluded. Results: A total of 643,131 COPD patients were included in the study, and only 12,308 patients developed PH during follow-up. Based on the inclusion and exclusion criteria, 8,577 PH patients were included in the cohort of patients with PH related to COPD for analysis. According to the definition of statin exposure, the final study population had 1,487 statin users and 7,090 statin non-users. The statin user group had a lower mortality related to PH than the non-user group (3.87 vs. 5.55 per 100 person-years, P<0.001). The mortality rate for PH in the multivariate analysis (aHR=0.78, 95% CI=0.62-0.98, P=0.046) was significantly lower for statin users than for non-users. Conclusion: Statins seem to benefit patients with PH and COPD.